Pharmacokinetic analysis reveals limitations and opportunities for nanomedicine targeting of endothelial and extravascular compartments of tumours. (3rd July 2019) - Benchimol, Michael J.; Bourne, David; Moghimi, Seyed Moein; Simberg, Dmitri
Abstract: Targeting of nanoparticles to tumours can potentially improve the specificity of imaging and treatments. We have developed a multicompartmental pharmacokinetic model in order to analyse some of the factors that control efficiency of targeting to intravascular (endothelium) and extravascular (tumour cells and stroma) compartments. We make the assumption that transport across tumour endothelium is an important step for subsequent nanoparticle accumulation in the tumour (area-under-the-curve, AUC) regardless of entry route (interendothelial and transendothelial routes) and study this through a multicompartmental simulation. Our model reveals that increasing endothelial targeting efficiency has a much stronger effect on the AUC than increasing extravascular targeting efficiency. Furthermore, our analysis reveals that both extravasation and intratumoral diffusion rates need to be increased in order to significantly increase the AUC of extravascular-targeted nanoparticles. Increasing the nanoparticle circulation half-life increases the AUC independently of extravasation and intratumoral diffusion. Targeting the extravascular compartment leads to a buildup in the first layer surrounding blood vessels at the expense of deeper layers (binding site barrier). This model explains some of the limitations of tumour targeting and provides important guidelines for the design of targeted nanomedicines.